The Smile of Truth : The French Satirical Eulogy and Its Antecedents - Tomarken, Annette H. (Book collections on Project MUSE., 2014)
To teach the truth smilingly was, during the Renaissance, a frequently expressed goal among prose writers and poets such as Erasmus, Berni, Ronsard, Rabelais, and du Bellay, who adopted an ironic posture within their mock encomia in order to refer the reader beyond the realm of the literary structure. In this book Annette Tomarken reconstructs the history of the classical satirical eulogy as it was revived, expanded, and finally adapted to new purposes in Renaissance literature. Tracing the development of this type of paradox from its classic roots through the Neo-Latin, Italian, and French.